Status and barriers impeding utilization of project management tools: epidemic for tripartite construction parties in Malaysia - Lee, Chia Kuang; Yiu, Tak Wing; Lim, Wei Xin; Adeleke, A. Q.; Toh, Tien Choon (KnE Social Sciences, 2019)
Project management tools have been widely used in construction project life cycles to monitor progress, evaluate payments/claims, and manage construction works worldwide. Despite their capability in helping project managers to achieve specific objectives within time, budget, and standards, not every construction organization in Malaysia would fully utilize these tools due to several challenges. As numerous studies substantiate the importance and of project management tools, lackluster adoption rates have led to productivity problems, project delays, and maturity problems at both project and enterprise levels in the construction industry. This study investigates the level of implementation and addresses the significant barriers that impede the utilization of project management tools. A survey was administered to well-known construction companies in Malaysia. This study revealed that the implementation level was discouragingly low, and the top 5 barriers were: (1) financial considerations, (2) restrictions on human capital, (3) high annual turnover, (4) lack of technology awareness, and (5) organizational culture. These findings suggest that the Malaysian construction industry should: overhaul financial and human resource limitations, increase assistance for users, and boost the partial implementation of basic techniques of project management to the maximum extent possible. The practitioners can understand the dynamics and causes of predicaments to the full implementation of project management tools in their respective companies. As for academicians, these findings help theoretical development and literature arguments on our current construction industry as a whole and optimistically help finds ways to make the Malaysian construction industry more efficient.